DIAGNÓSTICO DEL CLIMA LAbORAL ENTRE ADMINISTRATIvOS NOMbRADOS y CONTRATADOS DE LA FACULTAD DE CIENCIAS ADMINISTRATIvAS DE LA UNIvERSIDAD NACIONAL MAyOR DE SAN MARCOS - Fairlie Frisancho, Ebor (2013)
Concern for optimizing productivity in organizations and the increasing social value to the human system as the most important capital for organizational success determines the demand for services that are aware of the demand for services that allow the functioning of processes and outcomes related to job performance . A survey of office workers Faculty of Administrative Sciences of the Universidad Nacional Mayor de San Marcos and evaluated by the CL-WORK CLIMATE software that analyzes SPC 5 factors of self, JOB INVOLVEMENT, monitoring, communication and working conditions. The overall results show that the factor of self-realization is not complete, do not identify with management (policies), denotes labor and communication points are changed in a short time and working conditions fixed only until 2010. This survey was taken when he was still Dr. Roger Loayza as Dean and also influence management policies